Mosaic of conservation units: A conservation strategy for the Seridó Potiguar biome - Fontgalland, Isabel; Zenon Sabino de Oliveira, (Technium Sustainability, 2023)
This article aims to show the Seridó Potiguar - Brazil through the model of integrated management of conservation units and protected areas, known as area fragmentation mosaics. The loss of native vegetation, caused by anthropic destruction, is felt as one of the conditioning factors in the decrease of biodiversity almost everywhere on Earth, however, only with the creation of Conservation Units (UCs) will it be possible to establish a tool as a conservation strategy. The National System of Conservation Units (SNUC) began the structure in mosaics, where it could provide a participatory and social management of the territory of those involved, taking into account the conservation of biodiversity and geodiversity. In this way, this article observes to what extent a good management of UC mosaics can bring a better contribution to the conservation of biodiversity and geodiversity, taking into account particularly the Caatinga biome in the Seridó of the state of Rio Grande do Norte. As results, the project presents biophysical, socioeconomic and environmental elements. Keywords: Mosaic. Conservation Unit. Protected Area. Protected Area. Environment.